Pola Rekrutmen Politik Partai Keadilan Sejahtera (PKS) dalam Penentuan Caleg Perempuan pada Pileg 2014 di Kabupaten Grobogan - Andari, Pradita Tyas Putri; Adnan, Muhammad (Journal of Politic and Government Studies, 2018)
Now women's equality in politics has got own position, political progress that continues can grow women's representation in it, with a 30% quota giving a women space to deliver the aspirations of their group. But not all Political Parties pay attention to it, some women only meet the quota election requirements only. For women representatives to win or lose, it their own affairs. This research focuses on the pattern of political recruitment that executed by the Prosperous Justice Party to determine female cadres who are eligible to be nominated the 2014 District of Grobogan regency. The thought arises because until now the PKS can not deliver its women candidates to legislative seats in Grobogan District Council. This research uses descriptive qualitative research. Sources of data / subject of research are PKS officials, 5 female candidates with small seat number, and the society. Data collection was conducted byinterview there are 2 kinds of interviews, structured interviews and unstructured interviews. The sampling technique was purposive sampling.The result of the research is that PKS uses closed political recruitment pattern, the cadre can not elected herself but its nominated by the PKS, all the process is only Panjatida Team and internal member of PKS, recruitment is not publicized to the public. PKS seeks seeds from member of PKS. if it is less, then the party will recruit from external candidates with an individual approach. Other problems that makes women PKS candidates failed to obtain legislative candidate seats is a less strategic candidacy by nominating 2 people in one family, different with the area of residence, seat numbering system is not supported for women, less mobilization and passive female candidates. Keywords: Election, Political Party, Political Recruitment